A qualitative exploration of memory cuing by personal items in the home. (August 2019) - Zijlema, Annemarie; van den Hoven, Elise; Eggen, Berry
We are surrounded by personal items that can trigger memories, such as photos, souvenirs and heirlooms. Also during holidays, we collect items to remind us of the events, but not all bring back memories to the same extent. Therefore, we explored peoples' responses to personal items related to a holiday, using the home tour interviewing method. In total, 63 accounts of cuing responses from nine home tours were analysed using thematic analysis. This resulted in four types of cuing responses: (a) 'no-memory' responses, (b) 'know' responses, (c) 'memory evoked think or feel' responses and (d) 'remember' responses. For each of these cuing response categories, we looked into the types of items and their characteristics. Furthermore, we found that some items can evoke multiple memories. The majority of the memories' content refers to events close to the moment of acquiring the item.